Experience of Violence in the Lives of Homeless Persons: The Florida Four City Study, 2003-2004 - Wright, James D. ([Verlag nicht ermittelbar], 2010)
The primary goal of this study was to develop an understanding of the role of violence in the lives of homeless women and men. The objectives were to determine how many women and men have experienced some form of violence in their lives either as children or adults, the factors associated with experiences of violence, the consequences of violence, and the types of interactions with the justice system. The survey sample was comprised of about 200 face-to-face interviews with homeless women in each of four Florida cities (Jacksonville, Miami, Orlando, and Tampa). In all, 737 women were interviewed. In addition, 91 face-to-face interviews with homeless men were also conducted only in Orlando. For Part 1 (Female Interviews), the data include information related to the respondent's living conditions in the past month, as well as experiences with homelessness, childhood violence, adult violence, forced sexual situations, and stalking. Additional variables include basic demographic information, a self-report of criminal history, information related to how the respondent spent her days and evenings, and the physical environment surrounding the respondent during the day and evening. For Part 2 (Male Interviews), the data include much of the same information as was collected in Part 1. Information from Part 1 not included in Part 2 primarily includes questions pertaining to experience with forced sexual situations, and questions related to pregnancy and children.